No Referendum, No Election Campaign: How Radio Biafra Internet Broadcasting Mobilized IPOB Worldwide during the 2019 Nigerian Election - Nwafor, Gideon (The Journal of Society and Media, 2023)
In the buildup of 2019 general election in Nigeria, there were tensions in the Southeastern part of the country over the clamours for election boycott campaign initiated by the leader of the Indigenous People of Biafra (IPOB), Mazi Nnamdi Kanu, requesting that a referendum should hold in the region for the purpose of secession rather than conduct an election in the area. This drew critical attention nationwide and in diaspora as some rose to condemn the call while some supported the move. Few days to the election, the polity was heated up as to whether the Southeasterners will heed the clarion call to boycott the election or not with the IPOB foot soldiers on ground driving the campaign and threating mayhem to anyone who come out to vote until the “Supreme Leader” of IPOB called off the election boycott 24 hours to the election and there was total compliance and suspension of the campaign in the region. This could not have been possible without the effectiveness of Radio Biafra Internet broadcasting. How this Internet radio station was effective in the mobilization of members of IPOB to drive the “No Referendum, No Election” campaign is the focus of this study. Anchored on Technological Determinism theory, survey method was used to carry out the study with a population of 803,416 and a sample size of 382 listeners in Anambra and Abia States as respondents drawn using Krejcie and Morgan Sample Size Determination Table. The findings revealed that people were highly exposed to Radio Biafra No Referendum; No Election Campaign through Internet broadcasting on Facebook, Word of Mouth and Radio Biafra Terrestrial Broadcasting and this influenced their attitude toward 2019 election resulting to voter apathy in the area. Based on the findings, the researchers therefore, recommend that Radio Biafra should engage their digital broadcasting for national cohesion and integration rather than preach the message of secession disintegration